Sex-dependent effects of Cacna1c haploinsufficiency on juvenile social play behavior and pro-social 50-kHz ultrasonic communication in rats - Kisko, Theresa Marie; Witt, Stephanie; Rietschel, Marcella (Genes, brain and behavior, 2020)
As cross-disorder risk gene, CACNA1C is implicated in the etiology of all major neuropsychiatric disorders characterized by deficits in social behavior and communication and there is evidence for sex-dependent influences of single-nucleotide polymorphisms within CACNA1C on diagnosis, course, and recovery in humans. In this study, we aimed, therefore, at further exploring the role of Cacna1c in regulating behavioral phenotypes, focusing on sex-specific differences in social behavior and communication during the critical developmental period of adolescence in rats. Specifically, we compared rough-and-tumble play, concomitant emission of pro-social 50-kHz ultrasonic vocalizations, and social approach behavior in response to playback of 50-kHz ultrasonic vocalizations between constitutive heterozygous Cacna1c +/− females and wildtype Cacna1c +/+ littermate controls, and contrasted present female findings to data previously reported in males. Our results show for the first time that partial depletion of Cacna1c leads to sex-dependent alterations in social behavior and communication in rats. In females, Cacna1c haploinsufficiency led to hypermasculinization, with rough-and-tumble play behavior, in general, and pinning behavior, in particular, being even higher than in males without affecting concomitant 50-kHz ultrasonic vocalizations. In males, in contrast, rough-and-tumble play behavior was not altered, yet emission of 50-kHz ultrasonic vocalizations was diminished following partial Cacna1c depletion. The behavioral responses elicited by playback of 50-kHz ultrasonic vocalizations were reduced upon partial Cacna1c depletion in both sexes. It thus can be concluded that Cacna1c plays a prominent sex-dependent role in regulating juvenile rat social play behavior and pro-social 50-kHz ultrasonic communication with relevance to sex-specific effects seen in neuropsychiatric disorders.
First published: 27 December 2018
Gesehen am 12.02.2020